The Romantic Belief Their Relationship to Stockholm Syndrome - Al-Janaby, Safa; AlHusseini , Thuraya (Al-Adab Journal, 2024)
Although romance is a universal human condition, when it is driven by unfavorable thoughts and beliefs, it becomes irrational. As a result, people who seek treatment at psychiatric clinics experience a variety of issues, including uncontrollable emotions and behaviors that may have an impact on other areas of their lives and their decision-making in the future, these ideas, which have been influenced by romantic media since childhood, while being romantic about the connection could lead to some people developing Stockholm syndrome. Being a temporary survival mechanism of the subconscious, it manifests in cases of psychological trauma in order to ignore the flaws in their emotional partner, making them passively surrender to the partner and turn into a victim, the current study seeks to. Identify the Romantic Belief among patients who experience emotional issues; and Measure Stockholm syndrome in patients with emotional disorders based on two variables (sex, emotional state), The sample of the current study is (233) individuals who seek treatment at psychiatric clinics, Their ages range from (15-25 years). Following data collection and statistical analysis, the research findings led to the following conclusions: Romantic Belief, and Stockholm syndrome are statistically significant among visitors who experience emotional problems. In light of these findings, the study came to various conclusions and recommendations, including: conducting a training program to teach kids, teenagers, and young adults about self-confidence and enhancing their self-worth so they do not fear rejection by others, do not feel threatened by others leaving them, and realize that loving oneself is the most important thing to achieve happiness and that seeking love from others is not love but attachment.